Global Sourcing of Information Technology and Business Processes 4th Global Sourcing Workshop 2010, Zermatt, Switzerland, March 22-25, 2010, Revised Selected Papers - Oshri, Ilan.; Kotlarsky, Julia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book contains 14 carefully reviewed and selected papers from the 4th Workshop on Global Sourcing, held in Zermatt, Switzerland, March 22-25, 2010. They have been gleaned from a vast empirical base brought together by leading researchers of outsourcing and off shoring. This volume is intended for use by students, academics and practitioners interested in the outsourcing and off shoring of information technology and business processes. It offers a review of the key topics in outsourcing and off shoring, populated with practical frameworks that serve as a tool kit to students and managers. The sourcing models available to client firms are discussed in great depth. Vendor capabilities as well as client capabilities are studied and links are offered to the various sourcing models. Issues pertaining to knowledge and expertise are also discussed. Last but not least, the book examines current and future trends in outsourcing and off shoring, paying particular attention to the role that CIOs will play in shaping their sourcing strategies.
Strategic Orientation in the Globalization of Software Firms -- Strategic Sourcing of R&D: The Determinants of Success -- Exploring the Media Mix during IT-Offshore Project -- Parallel Transitions in IT Outsourcing: Making It Happen -- Management of Globally Distributed Software Development Projects in Multiple-Vendor Constellations -- Knowledge Integration in Global R&D Networks -- Portfolios of Control: Researching Discourses in IT Outsourcing -- Governance of Offshore IT Outsourcing at Shell Global Functions IT-BAM Development and Application of a Governance Framework to Improve Outsourcing Relationships -- Software-as-a-Service Vendors: Are They Ready to Successfully Deliver? -- Evolving Relationship Structures in Multi-sourcing Arrangements: The Case of Mission Critical Outsourcing -- Adaptability in IT Sourcing: The Impact of Switching Costs -- The Role of Contracts and Informal Relations in the Governance of IT Outsourcing Processes -- Living Labs: Arbiters of Mid- and Ground-Level Innovation -- Realising the Real Benefits of Outsourcing: Measurement Excellence and Its Importance in Achieving Long Term Value.
Keywords: Computer science; Software engineering; Information Systems; Business planning; Industrial procurement; Computer Science; Management of Computing and Information Systems; Software Engineering; Organization/Planning.; Procurement